Organisational Behaviour in the Workplace - Laurie J Mullins; Jacqueline E McLean (Slovakia Pearson, 2019)
Now a thoroughly modernised edition of Management & Organisational Behaviour the new Organisational Behaviour in the Workplace guides students through the person-organisation relationship by applying theories, developing critical thinking and engaging with case studies. This fully updated new edition is based on the individual, organisation, group and environment structure with a new focus on organisational behaviour: the understanding, prediction and control of human behaviour at work. Revised to incorporate new content and a focus on theory into practice, critical thinking and employability skills for student success. Key features include: - Overview topic map for the flow of topics and navigating the interrelation with topics in other chapters; - Organisational Behaviour in Action case studies throughout to give valuable insights into a practical real-world situation and active questions; - 'You' critical thinking questions to encourage self-reflection and active reading - New Critical Thinking Zone, written by practitioner Dr Jacqueline McLean, with activities to develop critical thinking for example through different viewpoints in articles; - Personal skills and employability sections to help you to develop your social and work-based skills in preparation for life after study - Conceptual mind maps of complex topics to aid understanding and revision; - Student companion website with further information, self-test questions and videos; - Organisational Behaviour in the Workplace will appeal to students at undergraduate level or on related professional courses, as well as to graduates and professionals aspiring to management positions.
Age Group: Adult
Keywords: Organizational behavior; Psychology; Management; Textbooks